The burden of hepatitis C virus in the world, China, India, and the United States from 1990 to 2019 - Yang, Jia; Qi, Jin-Lei; Wang, Xiao-Xiao; Li, Xiao-He; Jin, Rui; Liu, Bai-Yi; Liu, Hui-Xin; Rao, Hui-Ying (Frontiers in Public Health, 2023)
Background and aim Hepatitis C virus infection can lead to an enormous health burden worldwide. Investigating the changes in HCV-related burden between different countries could provide inferences for disease management. Hence, we aim to explore the temporal tendency of the disease burden associated with HCV infection in China, India, the United States, and the world. Methods Detailed data on the total burden of disease related to HCV infection were collected from the Global Burden of Disease (GBD) 2019 database. Joinpoint regression models were used to simulate the optimal joinpoints of annual percent changes (APCs). Further analysis of the age composition of each index over time and the relationship between ASRs and the socio-demographic Index (SDI) were explored. Finally, three factors (population growth, population aging, and age-specific changes) were deconstructed for the changes in the number of incidences, deaths, and DALYs. Results It was estimated that 6.2 million new HCV infections, 0.54 million HCV-related deaths, and 15.3 million DALYs worldwide in 2019, with an increase of 25.4, 59.1, and 43.6%, respectively, from 1990, are mainly due to population growth and aging. China experienced a sharp drop in age-standardized rates in 2019, the United States showed an upward trend, and India exhibited a fluctuating tendency in the burden of disease. The incidence was increasing in all locations recently. Conclusion HCV remains a global health concern despite tremendous progress being made. The disease burden in China improved significantly, while the burden in the United States was deteriorating, with new infections increasing recently, suggesting more targeted interventions to be established to realize the 2030 elimination goals.